(untitled) (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2026)
This study aims to explore how Instagram-supported writing instruction influences vocational high school students’ writing development and engagement in an Indonesian EFL context, identify the aspects of writing most affected, and examine the challenges encountered during the learning process. Adopting a qualitative descriptive design, the study involved 20 eleventh-grade vocational students from a vocational high school in West Java, Indonesia. Data were collected through classroom observations, document analysis of students’ Instagram posts, and semi-structured interviews with selected students and the teacher. The data were analyzed thematically to capture recurring patterns related to writing development, engagement, and learner perceptions. The findings indicate that Instagram-supported instruction positively enhanced students’ engagement, confidence, and motivation to write. Students demonstrated noticeable improvement in creativity, relevance, and coherence of writing, supported by Instagram’s multimodal affordances and authentic audience interaction. However, grammatical accuracy and vocabulary limitations remained challenges, highlighting the need for pedagogical scaffolding. The study implies that integrating Instagram into EFL writing instruction can support vocationally relevant writing practices when combined with guided feedback and instructional support.